A Domain Based Approach to Semantic Lexicon Expansion. (4th December 2021) - Prentice, Sheryl; Rayson, Paul; Knight, Jo; El-Haj, Mahmoud; Elstein, Solly
Abstract: Current approaches to the expansion of semantic lexicons for corpus annotation are somewhat ad hoc in nature and do not generally offer a systematic means of identifying areas for development within one's lexicon. The present paper sets forward a domain based approach to semantic lexicon expansion, targeting UCREL's Semantic Analysis System (USAS). First, an updated version of the lexicon is compared to representative corpora to ascertain areas of underrepresentation in a novel method which we call K-FLUX analysis. Second, an example set of underrepresented types are targeted for development using domain specific corpora. Collectively, the results show that some corpora are more successful than others in supplementing the existing USAS lexicon. The paper discusses the various factors that should be borne in mind when utilising the proposed method before concluding with how findings might inform future developments of the lexicon, and crucially, the semantic system on which it is based.